A study into the prevalence of diatoms in the soft Drinks in Malaysia - Hasan, Mohd.Khairul Anuar Mohd (Universiti Sains Malaysia, 2006)
Drowning is defined as death due to immersion or partial immersion in a liquid and it is one of the most common causes of unnatural death. A large volume of water is absorbed into the circulation because the low salt (sodium chloride) in the freshwater. Together with the water inhaled, diatoms are also inhaled reaching throughout circulation. Pathologists are often faced with the problem, while examining the dead body taken from the water, when asked whether the case was one of drowning or was the victim dead before entering the water? In a situation in which the dead body is highly decomposed or only the skeletal remains are recovered, direct diagnosis of death by drowning is indeed difficult. In highly decomposed dead body, when there is nothing left except those skeletal remains, and in which there is no tissue remains, histopathological examination can not be done, and the only method left is considered to be diatom test. However, many researchers have demonstrated diatoms in tissue samples from non- drowned individuals. The channel through which the diatoms reach the internal organs seems primarily through the lungs. Respired air normally contains a fairly large number of diatoms cells and valves. Also through the alimentary canal when there is a possibility of presence of diatoms in the food. Raw fruit and vegetables which have been in contact with soil diatom and shellfish which feed on diatoms contains diatoms. In this research, only juicy drink sold in restaurants are considered for analysis. The result shows the absence of diatoms in all the drink samples examined here. It is possible that